JOB SATISFACTION ON JOB PERFORMANCE OF EMPLOYEES IN INFORMATION TECHNOLOGY INDUSTRY - Donthu, Dr. Somasekhar; Subramanyam, Dr. P. (The journal of contemporary issues in business and government, 2022)
This research article aims to “To measure the impact of key predictors of job satisfaction on job performance of employees in IT industry”. The paper applies data reduction using Confirmatory Factor Analysis (CFA) on a sample of 364 respondents drawn from IT industry in the Bengaluru and condenses a set of 12 job satisfaction items converted into a four key predictors. The present study proposes a model of the impact of key predictors of job satisfaction on job performance. The study found that pay, supervision, work itself and promotion are impacting significantly the job performance. Therefore, IT companies should focus on the above factors to job performance of employees. The study investigated the impact of key predictors of job satisfaction on job performance of the employees in IT industry concluded that pay had the highest impact on the job performance of the employees’ supervision, work itself followed by promotions.